2021
DOI: 10.1101/2021.05.20.445000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional dissection of human mitotic genes using CRISPR-Cas9 tiling screens

Abstract: Kinetochores are large protein assemblies that mark the centromere and bind to mitotic spindle microtubules to ensure accurate chromosome segregation. Like most protein-coding genes, the full multifunctional nature of kinetochore factors remains uncharacterized due to the limited experimental tools for unbiased dissection of human protein sequences. Here, we develop a method that leverages CRISPR-Cas9 induced mutations to comprehensively identify key functional regions within protein sequences that are require… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…How Mad1 interacts with RZZ is not known yet. A recent study identified a region on Mad1 to be involved in interacting with RZZ has shed light on this question (Herman et al, 2021). The mechanism of RZZ-Mad1 facilitating Bub1-Mad1 interaction is also missing.…”
Section: Bub1-rzz Interaction May Contribute To Spindle Assembly Chec...mentioning
confidence: 99%
“…How Mad1 interacts with RZZ is not known yet. A recent study identified a region on Mad1 to be involved in interacting with RZZ has shed light on this question (Herman et al, 2021). The mechanism of RZZ-Mad1 facilitating Bub1-Mad1 interaction is also missing.…”
Section: Bub1-rzz Interaction May Contribute To Spindle Assembly Chec...mentioning
confidence: 99%